2021
DOI: 10.1136/bmjopen-2021-052170
|View full text |Cite
|
Sign up to set email alerts
|

Awareness and attitudes towards advance care planning in primary care: role of demographic, socioeconomic and religiosity factors in a cross-sectional Lebanese study

Abstract: ObjectiveTo assess awareness and attitudes towards engaging in advance care planning (ACP) and their relationship with demographic, socioeconomic and religiosity factors among Lebanese middle-aged to older-aged adults in primary care.DesignA cross-sectional survey study.SettingTertiary referral hospital in Beirut, Lebanon.ParticipantsA total of 215 middle-aged to older-aged adults.ResultsOut of 215 participants, 18.6% of participants knew about ACP; 94% favoured truth-telling; 87.4% favoured healthcare autonom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…Women were also more aware of ACP than men. Men had higher willingness to perform life-prolonging interventions [ 24 ]. In the study by Yunus et al 56.2% to 72.6% of American Muslims were in the pre-thinking stage about ACP and mainly were unprepared to interact with the concept of ACP.…”
Section: Introductionmentioning
confidence: 99%
“…Women were also more aware of ACP than men. Men had higher willingness to perform life-prolonging interventions [ 24 ]. In the study by Yunus et al 56.2% to 72.6% of American Muslims were in the pre-thinking stage about ACP and mainly were unprepared to interact with the concept of ACP.…”
Section: Introductionmentioning
confidence: 99%
“…However, other research studies have shown that low income is positively correlated with HPC awareness, suggesting that people with low income are more willing to seek alternative options because of the high cost of curative treatment [ 45 ]. One study has also reported that income is not significantly related to awareness of ACP [ 19 ]. Our study showed that female participants were less likely to be aware of ACP than male participants, whereas gender had no significant relationship with awareness of HPC.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, as the world faces an aging population and an increasing in number of patients with chronic and incurable diseases, strategies to increase awareness and promote the use of ACP and HPC are becoming important for improving quality of care [ 19 , 20 ]. The percentage of people aged 65 years or more of the world is projected to increase from 9.8% in 2022 to 20.1% in 2070 [ 21 ].…”
Section: Introductionmentioning
confidence: 99%